NEW UKARINIAN SCHOOL EDUCATIONAL REFORMS AND PROFFESSIONAL MASTERSHIP OF THE PHYSICAL EDUCATION TEACHER - Sorokolit, Nataliya; Lukjanchenko, Mykola; Turchyk, Iryna; Chopyk, Roman (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The physical education teachers’ attitude towards reforming of education in Ukraine in terms of reform “New Ukrainian School” was analyzed in the article. The physical education specialists’ thoughts according these reforms’ impact on forming of professional mastership of teachers were analyzed in the article. The goal of the research is to provide comparable analysis of the support level of New Ukrainian School reforms that have impact on building professional improvement of physical education teachers. In order to reach the goal such methods were applied as analysis and generalization of literature sources, teachers’ survey, based on questionnaire, its mathematic processing and comparative analysis. There were questioned 341 teachers from 7 Ukrainian regions with different qualification levels and pedagogical experience. All the respondents have given their permission in participation in the research. The different levels of support of educational reforms among physical education teachers were found out. Innovations, in general, have higher than average and lower than average levels of support. The highest level of support has such innovation as freedom to choose or create educational program – 77,4%. However, even with high level of support, 41,9% of teachers think that they should teach pupils according to the only studying program, that is submitted by profile ministry. Only 6,5% of respondents are ready to create their own studying programs. However, 33,8% of teachers think the studying program should be adapted according to conditions of educational establishments. In order to build professional mastership, it is essential to imply different forms of qualification improvements (71,3%), distance studying during course retraining (59,7%), teachers’ certification (53,6%). The lowest level of support has decentralization in management of educational establishment (39,1%).